Lennart Lundmark; Uppbörd, utarmning, utveckling. Det samiska fångstsamhällets övergång till rennomadism i Lule Lappmark - Editor, Editor (Rangifer, 1982)
Dissertation in Swedish defended at the University of Umeå 28 May 1982. The aim of the work is to study the changeto reindeer nomadism in the Lule Lapp region.